2004
DOI: 10.2460/javma.2004.225.1716
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features of an unusual outbreak of cryptococcosis in dogs, cats, ferrets, and a bird: 38 cases (January to July 2003)

Abstract: Serologic titers were beneficial in identifying infection in animals with nonspecific signs, but routine serum biochemical or hematologic parameters were of little value in diagnosis. Most animals had nonspecific CNS signs and represented a diagnostic challenge. Animals that travel to or live in this region and have nonspecific malaise or unusual neurologic signs should be evaluated for cryptococcosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
102
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 25 publications
4
102
0
2
Order By: Relevance
“…In Canada, a multivariate survival analysis revealed that CNS infection but not respiratory disease or other medical history was a significant predictor of mortality (171). Retroviral infection in cats does not appear to predispose them to cryptococcosis (172). The prevalence of C. gattii infection in cats with feline immunodeficiency virus or feline leukemia virus infection is not known.…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Canada, a multivariate survival analysis revealed that CNS infection but not respiratory disease or other medical history was a significant predictor of mortality (171). Retroviral infection in cats does not appear to predispose them to cryptococcosis (172). The prevalence of C. gattii infection in cats with feline immunodeficiency virus or feline leukemia virus infection is not known.…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%
“…These aspects are not reviewed, but the salient features of C. gattii infection in various animals are presented. Case reports and moderate-to-large case series of C. gattii in cats abound (37,169,(171)(172)(173)(176)(177)(178)(179)(180)(181)(182). A review of the major studies where the etiologic cryptococcal species were reported indicates that there are no clinical features which reliably distinguish disease caused by C. neoformans from that due to C. gattii.…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cats and dogs with cryptococcosis are often treated with fluconazole monotherapy because of its relatively low cost, ease of administration, and favorable pharmacokinetic properties. Response to treatment can be slow or inadequate, and reported rates of successful disease control or cure range from 7 to 100% in cats and 27% in dogs (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The incidence in cats is, in fact, far higher than in other domestic species and fastidious grooming behaviour as well as the breathing pattern of cats could contribute to increased delivery of the fungus to the nasal cavity, or the difference may relate to species-specific host 11 There were a total of 119 cases of feline cryptococcosis for which the original presenting clinical signs were recorded: 39.5% cats presented with CNS signs, 28% had pulmonary or other respiratory signs, 25% had skin or nasal granulomas, while 3.3% had mandibular lymph node enlargement, 2.5% presented with gastrointestinal signs and 1.7% had renal signs. Forty-six cases were typed; 42 of these were C. gattii VGIIa while four cases, all with skin granulomas, were C. neoformans var.…”
mentioning
confidence: 99%